Survival and Nesting Ecology of Scaled Quail in the Trans-Pecos, Texas - Carlos E. Gonzalez Gonzalez; Louis A. Harveson; Ryan S. Luna (National Quail Symposium Proceedings, 2017)
Scaled quail (Callipepla squamata) are one of the most ecologically and economically important wildlife species in the Trans-Pecos, because they are the primary upland game bird in the Chihuahuan Desert. Using radiotelemetry, we evaluated survival (Kaplan–Meier) and nesting success of quail on 3 study sites in the Trans-Pecos, Texas: one (Santiago Mountain Ranch, central Brewster Co.) was supplemented with milo (Sorghum bicolor) year-round, the second (Lado Ranch, south Culberson Co.) never used supplements, and the third (Apache Ranch, central Culberson Co.) was supplemented with quail blocks. We trapped and radiocollared 164 female quail collectively across all study sites, and followed them for 2 years (May–Sep 2012–2013). There were no survival differences between years within study sites (P = 0.985), so we grouped data across years and compared survival between study sites. Apache Ranch had the lowest survival (55%) compared with the Santiago Mountain Ranch (76.3%) and Lado Ranch (75%). We found 47 nests across the reproductive seasons for 2012 and 2013. On average, scaled quail had high nesting success (72.6%), eggs per nest (11.6), and hatchability (91.25%). Nesting occurred from May to September with peak nesting in June and July. Timing and quantity of rain, combined with range conditions seemed to have the greatest effect on nesting performance.
Keywords: callipepla squamata; nesting; scaled quail; survival